Gay affirmative practices among healthcare professionals in Poland and Spain: results of Health Exclusion Research in Europe (HERE) study - Karniej, Piotr; Dissen, Anthony; del Pozo-Herce, Pablo; Juárez-Vela, Raúl; Martínez-Sabater, Antonio; Gea-Caballero, Vicente; Echaniz-Serrano, Emmanuel; Santolalla-Arnedo, Iván; Czapla, Michał (Frontiers in Public Health, 2025)
IntroductionHealthcare professionals play a critical role in providing affirmative care to gay and lesbian patients. However, their attitudes and practices can vary significantly depending on cultural and educational contexts. This study aimed to evaluate differences in affirmative practices among healthcare professionals in Poland and Spain, focusing on their approach to these patient groups, utilizing the Gay Affirmative Practice (GAP) Scale, as well as identifying key factors influencing these practices.MethodsA cross-sectional study was conducted among healthcare professionals in Poland and Spain using the GAP Scale, which assesses beliefs and behaviors toward gay and lesbian patients. Data collection included 495 participants, with 205 from Spain and 290 from Poland. Descriptive statistics, Mann–Whitney tests, and multivariate regression analyses were used to identify factors associated with affirmative practices.ResultsSpanish participants scored significantly higher on both the beliefs and behaviors scales compared to Polish participants (p < 0.001 and p = 0.009, respectively). Gender of healthcare providers was a significant factor in both groups, with women demonstrating more affirmative beliefs than men. In the Polish group, being male was associated with a decrease in the belief scale score by an average of 6.572 points (regression coefficient = −6.572, p < 0.001), while attending LGBT-related training 1–2 times was associated with an increase of 5.356 points on the belief scale (regression coefficient = 5.356, p = 0.039). No significant independent predictors were identified for behaviors in the Polish group, as all p-values exceeded 0.05.ConclusionSpanish healthcare professionals showed more affirmative practices toward gay and lesbian patients than their Polish counterparts. Sex and gay and lesbian related training influenced beliefs, with male sex linked to lower affirmative practice in Poland. These findings highlight the need for systematic integration of gay and lesbian specific training into healthcare education programs to foster cultural competence and reduce disparities in patient care.